2010
DOI: 10.1152/japplphysiol.00725.2010
|View full text |Cite
|
Sign up to set email alerts
|

Heat acclimation improves cutaneous vascular function and sweating in trained cyclists

Abstract: The aim of this study was to explore heat acclimation effects on cutaneous vascular responses and sweating to local ACh infusions and local heating. We also sought to examine whether heat acclimation altered maximal skin blood flow. ACh (1, 10, and 100 mM) was infused in 20 highly trained cyclists via microdialysis before and after a 10-day heat acclimation program [two 45-min exercise bouts at 50% maximal O2 uptake (V̇o2max) in 40°C ( n = 12)] or control conditions [two 45-min exercise bouts at 50% V̇o2max in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 54 publications
6
104
2
Order By: Relevance
“…It is possible that under heat stress, any reduction in skeletal muscle energy consumption were too small for these measures to detect or, from a haemodynamic perspective, skeletal muscle may not be sensitive to further increases in NO following IP, due to the apparently greater role of prostaglandins, relative to NO for inducing vasodilation (Kellogg et al 2005). Moreover, it is possible that blood vessels are already maximally dilated from heat stress (Lorenzo & Minson 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that under heat stress, any reduction in skeletal muscle energy consumption were too small for these measures to detect or, from a haemodynamic perspective, skeletal muscle may not be sensitive to further increases in NO following IP, due to the apparently greater role of prostaglandins, relative to NO for inducing vasodilation (Kellogg et al 2005). Moreover, it is possible that blood vessels are already maximally dilated from heat stress (Lorenzo & Minson 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, 10 of 11 studies demonstrated that heat stress decreased VO 2max by a mean of -11%. Heat acclimatization status did not moderate the VO 2max decrease from temperate to hot conditions (160,270). Arngrimsson et al (15) were the only investigators to examine the impact of graded heat stress (in the same subjects) and found an inverse relationship (r = -0.77) between ambient temperature and VO 2max .…”
Section: History Of Research Related To Aerobic Performancementioning
confidence: 96%
“…The discrimination between these two mechanisms is not possible as they overlap each other. Nevertheless, Lorenzo & Minson have shown that skin microcirculation also undergoes thermoadaptative changes as a part of acclimation to heat without eliciting reflexes engaged in exercise (Lorenzo & Minson, 2010). To do so, they trained subjects only at 50% of their V O2max , intensity that assumingly does not induce changes in the reflexes affecting exercise.…”
Section: Exercise Augments the Endothelium Dependent Vasodilation In mentioning
confidence: 99%